ISTILAH-ISTILAH MAKANAN DALAM BAHASA INGGRIS DAN BAHASA PATANI (SUATU ANALISIS KONTRASTIF) - Ishak, Fariana; Pamantung, Rina P.; Sigarlaki, Stephani J. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â ABSTRACTÂ  Â  Â This research is entitled â€œThe Terms of Food in English and Patani Language: A Contrastive Analysisâ€. This reseacrh is an attempt to identify, classify, analyze and describe the terms of food which are used in English and panati language. The English data have been collected from thesis and from the internet, whereas the Patani language data have been elicted from some informants. The qualitative descriptive method is used to describe and analyze the kinds of food by using Frisch in Hickerson theory. After describing the kind of food in English and Patani language, the writer makes a contrastive analyze by using Robert Lado theory in finding out the similarities and diffrences of both Language. In this research the writer uses Givon (1994) and Leechâ€™s theory (1971) to analyzing the data, and Lado (1957) theory to contrasting both languages to find out the differences and similarities. The result shows that the kind of terms of food in English and Patani language consists of two groups, they are solid food and oil food. Solid food consists of fruits, vegetable, bread, meat, fish and seafood, and proccesed food. The form of food in Panati are liquid and solid food. English food term consist of word and phrase and the meaning only denotative. Patani society has so many celebrations that used the certain name. Word, phrase, and clause as lingual forms of Panati food. The meaning are denotative and connotative meaning.Keywords: The Terms of Food in English and Patani Language, Contrastive Analysis